Restaurant Inspection Reports as a Proxy Measure for Occupational Health and Safety: South Asian Restaurant Workers in New York City. Issue 3 (31st August 2018) - Nabeel, Ismail; Alamgir, Hasanat
There is a great need to develop workplace health and safety surveillance systems for small businesses to systematically understand the cause, nature, and severity of injuries and illness of their workers. Restaurants can be hazardous workplaces for the nature of the business, materials handled, and tasks completed. Some of the traditional South Asian establishments/restaurants rely heavily on the traditional way of food preparation. Workers in these places may work in less than ideal conditions with minimal or no workplace health and safety regulations or programs. We have explored a unique idea of using NYC's restaurant inspection reports as a possible surveillance tool using the overall restaurant grade and specific violations. Findings show 19% of the Indian, 26% of Bangladeshi, and 15% of Pakistani restaurants did not achieve grade A in these inspections suggesting that around 20% of these restaurants workers are more likely to work in a relatively hazardous or unhygienic working conditions. Using restaurant inspection grade as a proxy measure for employee safety and working conditions may prove to be a useful and practical measure for such an industry.